ANALYSIS OF THE IMPACT OF REVIEWS, RATINGS AND FREE SHIPPING PROMOTIONS ON CONSUMER SATISFACTION OF THE TIKTOK SHOP APPLICATION ON PT. BPR PRIMA MADANI MEDAN - Suci Sundari Piliang; Winda Sri Astuti Doloksaribu; Vincent Jonery Ng; Jansen Salim; Acai Sudirman (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study was conducted to examine the influence of reviews, ratings, and free shipping promotions on consumer satisfaction in the TikTok Shop application. The respondents in this study were 38 employees of PT. BPR PRIMA MADANI. This study used SMART PLS data processing to determine whether the variables were valid and reliable, and whether each independent variable positively affected the dependent variable or not. The results of this study indicate that the review variable has a partial effect on the consumer satisfaction variable, with a T-statistic value of 2.269 > 1.96 and a P-value of 0.024 < 0.05. The rating variable does not have a partial effect on the consumer satisfaction variable, as the test results for the rating variable show a T-statistic value of 1.112 < 1.96 and a P-value of 0.267 > 0.05. The free shipping variable has a partial effect on the consumer satisfaction variable, with test results showing a T-statistic value of 2.905 > 1.96 and a P-value of 0.004 < 0.05. However, the results of the F-test with an NFI value of 0.716 > 0.062 indicate that the variables of review, rating, and free shipping promotions simultaneously influence the consumer satisfaction variable in the TikTok Shop application among the employees of PT. BPR PRIMA MADANI Medan.